Reproductive ethogram and mate selection in captive wild Senegalese sole (Solea senegalensis) - Carazo, Ignacio; Chereguini, Olvido; Martín, Ignacio; Huntingford, Felicity; Duncan, Neil (Spanish Journal of Agricultural Research, 2016)
Senegalese sole (Solea senegalensis) have a high potential for aquaculture that is hampered by reproductive behavioural problems. These problems result in limited breeder participation in spawning. The present study provided an ethogram and described mate selection and spawning of captive wild Senegalese sole. Two tanks of breeders were studied that had 29 and 25 breeders (mean weight = 1.6 ± 0.1 kg). The behaviour was studied during 20 periods of 24 hours: 10 periods where spawning events were recorded and 10 control periods without spawning events. Periods where spawning occurred had three times more locomotor activity than periods without spawning. Two distinct behaviours, termed the “following” behaviour and the “coupled swim”, were only observed during periods with spawning. The courtship sequence (n=12) began with males predominantly involved in “following” behaviours, whilst females remained mainly stationary on the bottom of the tank. Males rested on the females and encouraged the females to begin swimming. When the female began to swim the male swam under the female and the pair made a “coupled swim” to the surface to release gametes. Gamete release was strictly in pairs of one male with one female. Failed “coupled swims” without gamete release were 5.6 times more frequent than successful “coupled swims”. Mate selection was evident as the sole engaged in: paired spawning, males displayed to females, males encouraged females to spawn and females accepted or rejected the male’s advances. The mate selection process provided the opportunity for fish to dominate the spawning and also demonstrated how fish were excluded from spawning.